2016
DOI: 10.1371/journal.pone.0158370
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Measurement of Anomie

Abstract: Sociologists coined the term “anomie” to describe societies that are characterized by disintegration and deregulation. Extending beyond conceptualizations of anomie that conflate the measurements of anomie as ‘a state of society’ and as a ‘state of mind’, we disentangle these conceptualizations and develop an analysis and measure of this phenomenon focusing on anomie as a perception of the ‘state of society’. We propose that anomie encompasses two dimensions: a perceived breakdown in social fabric (i.e., disin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
123
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(157 citation statements)
references
References 87 publications
(150 reference statements)
13
123
0
6
Order By: Relevance
“…Anomie is used to describe societies experiencing upheaval and instability as a result of war or revolution (Heydari, Teymoori, Haghish, & Mohamadi, ) but also due to rapid economic changes or crises (Messner & Rosenfeld, ). Teymoori and colleagues () proposed a conception of anomie as a reflection of the state of society in the minds of individuals, specifically the view that the social and political conditions in society are falling apart and that there is a lack of trust and moral standards. Neoliberal policies often include cuts to social security and benefits and make demands on the flexibility and mobility of the workforce in the name of individual responsibility and self‐reliance.…”
Section: The Rise Of Neoliberalismmentioning
confidence: 99%
See 2 more Smart Citations
“…Anomie is used to describe societies experiencing upheaval and instability as a result of war or revolution (Heydari, Teymoori, Haghish, & Mohamadi, ) but also due to rapid economic changes or crises (Messner & Rosenfeld, ). Teymoori and colleagues () proposed a conception of anomie as a reflection of the state of society in the minds of individuals, specifically the view that the social and political conditions in society are falling apart and that there is a lack of trust and moral standards. Neoliberal policies often include cuts to social security and benefits and make demands on the flexibility and mobility of the workforce in the name of individual responsibility and self‐reliance.…”
Section: The Rise Of Neoliberalismmentioning
confidence: 99%
“…Teymoori et al. () found that anomie was linked to disidentification from the superordinate group, in their case measured as national identification. They concluded that the superordinate group is seen as a source of negative identity because it does not successfully manage social harmony.…”
Section: The Rise Of Neoliberalismmentioning
confidence: 99%
See 1 more Smart Citation
“…Al no poder la sociedad regular las pasiones individuales, aparece el suicidio anómico, muestra de que las dinámicas que carecen de reglamentación y no se vinculan con las condiciones propias de la vida social a las que deben responder, no pueden evitar colisionar dolorosamente. Por esto, Reyes (2016) Existe una amplia gama de instrumentos que se han desarrollado para medir la anomia, e incluso hoy en día todavía se siguen desarrollando (Fandiño, Souza, Formiga, Menezes, & Bentes, 2015;Levina & Mārtinsone, 2017;Teymoori, 2016;Teymoori et al, 2016). Uno de los primeros instrumentos que se desarrollaron fue la Escala de Srole (1956), la cual se aproxima a la anomia desde los diversos aspectos psicológicos relacionados con ésta (Vera, Camino, Formiga, Yáñez & Bautista, 2013).…”
Section: Ntroducciónunclassified
“…for the study of group processes are discussed. 4 The data of Study 3, the international survey, was collected by our colleagues who are co-authors of this manuscript that has been recently published in PLOS ONE: Teymoori, A., Jetten, J., Bastian, B., Ariyanto, A., Autin, F., Ayub, N., Badea, C., Besta, T., Butera, F., Costa-Lopes, R., Cui, L., Fantini, C., Finchilescu, G., Gaertner, L., Gollwitzer, M., Gómez, A., González, R., Hong, Y., Jensen, D., Karasawa, M., Kessler, T., Klein, O., Lima, M., Mähönen, T., Megevand, L., Morton, T., Paladino, P., Polya, T., Ruza, A., Shahrazad, W., Sharma, S., Torres, A., van der Bles, A., & Wohl, M. (2016). Revisiting the measurement of anomie.…”
Section: What Does a Psychological Analysis Of Anomie Have To Offer?mentioning
confidence: 99%